Frederick Douglass papers - Douglass, Frederick, 1818-1895.; Douglass, Helen, 1838-1903.
Correspondence, diary (1886-1887), speeches, articles, manuscript of Douglass's autobiography, financial and legal papers, newspaper clippings, and other papers relating primarily to his interest in social, educational, and economic reform; his career as lecturer and writer; his travels to Africa and Europe (1886-1887); his publication of the North Star, an abolitionist newspaper, in Rochester, N.Y. (1847-1851); and his role as commissioner (1892-1893) in charge of the Haiti Pavilion at the World's Columbian Exposition in Chicago. Subjects include civil rights, emancipation, problems encountered by freedmen and slaves, a proposed American naval station in Haiti, national politics, and women's rights. Includes material relating to family affairs and Cedar Hill, Douglass's residence in Anacostia, Washington, D.C.
Includes correspondence of Douglass's first wife, Anna Murray Douglass, and their children, Rosetta Douglass Sprague and Lewis Douglass; a biographical sketch of Anna Murray Douglass by Sprague; papers of his second wife, Helen Pitts Douglass; material relating to his grandson, violinist Joseph H. Douglass; and correspondence with members of the Webb and Richardson families of England who collected money to buy Douglass's freedom.
Correspondents include Susan B. Anthony, Ottilie Assing, Harriet A. Bailey, Ebenezer D. Bassett, James Gillespie Blaine, Henry W. Blair, Blanche Kelso Bruce, Mary Browne Carpenter, Russell Lant Carpenter, William E. Chandler, James Sullivan Clarkson, Grover Cleveland, William Eleroy Curtis, George T. Downing, Rosine Ame Draz, Paul Laurence Dunbar, Timothy Thomas Fortune, Henry Highland Garnet, William Lloyd Garrison, Martha W. Greene, Julia Griffiths, John Marshall Harlan, Benjamin Harrison, George Frisbie Hoar, J. Sella Martin, Parker Pillsbury, Jeremiah Eames Rankin, Robert Smalls, Gerrit Smith, Elizabeth Cady Stanton, Lucy Stone, Henry Ossawa Tanner, Theodore Tilton, John Van Voorhis, Henry O. Wagoner, and Ida B. Wells-Barnett.
Available through the Library of Congress Web site.
Microfilm edition available
Microfilm edition (no. 10,997) produced from originals at the Frederick Douglass Memorial Home. Material on this microfilm later transferred to Library of Congress Manuscript Division and included in Microfilm 16,377.
Microfilm edition (no. 16,377) produced from originals in the Manuscript Division.
In part, photocopies.
Library of Congress Prints and Photographs Division.
Keywords: Anthony, Susan B. -- 1820-1906 -- Correspondence; Assing, Ottilie -- Correspondence; Bailey, Harriet A. -- Correspondence; Bassett, Ebenezer D., -- 1833-1908 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Blair, Henry W. -- 1834-1920 -- Correspondence; Bruce, Blanche Kelso, -- 1841-1898 -- Correspondence; Carpenter, Mary Browne, -- active 1862-1894 -- Correspondence; Carpenter, Russell Lant, -- 1816-1892 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Clarkson, James Sullivan, -- 1842-1918 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Curtis, William Eleroy, -- 1850-1911 -- Correspondence; Douglass, Anna Murray, -- -1882.; Douglass, Anna Murray, -- -1882 -- Correspondence; Douglass, Lewis, -- 1840-1908 -- Correspondence; Douglass, Joseph H. -- 1871-1935.; Downing, George T. -- 1819-1903 -- Correspondence; Draz, Rosine Ame -- Correspondence; Dunbar, Paul Laurence, -- 1872-1906 -- Correspondence; Fortune, Timothy Thomas, -- 1856-1928 -- Correspondence; Garnet, Henry Highland, -- 1815-1882 -- Correspondence; Garrison, William Lloyd, -- 1805-1879 -- Correspondence; Greene, Martha W. -- Correspondence; Griffiths, Julia, -- -1895 -- Correspondence; Harlan, John Marshall, -- 1833-1911 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hoar, George Frisbie, -- 1826-1904 -- Correspondence; Martin, J. Sella -- 1832- -- Correspondence; Pillsbury, Parker, -- 1809-1898 -- Correspondence; Rankin, Jeremiah Eames, -- 1828-1904 -- Correspondence; Richardson family -- Correspondence; Smalls, Robert, -- 1839-1915 -- Correspondence; Smith, Gerrit, -- 1797-1874 -- Correspondence; Sprague, Rosetta Douglass -- Correspondence; Stanton, Elizabeth Cady, -- 1815-1902 -- Correspondence; Stone, Lucy, -- 1818-1893 -- Correspondence; Tanner, Henry Ossawa, -- 1859-1937 -- Correspondence; Tilton, Theodore, -- 1835-1907 -- Correspondence; Van Voorhis, John, -- 1826-1905 -- Correspondence; Wagoner, Henry O. -- Correspondence; Webb family -- Correspondence; Wells-Barnett, Ida B., -- 1862-1931 -- Correspondence; North star (Rochester, N.Y.); African American newspapers -- New York (State) -- Rochester; African Americans -- Washington (D.C.); Civil rights; Educational change; Exhibitions -- Illinois -- Chicago; Freedmen; Navy-yards and naval stations, American -- Haiti; Slavery; Slaves -- Emancipation; Social problems; Women's rights; Africa -- Description and travel; Anacostia (Washington, D.C.) -- History; Europe -- Description and travel; United States -- Economic conditions -- 19th century; United States -- Politics and government -- 19th century